Practical debugging at scale : cloud native debugging in Kubernetes and production - Almog, Shai (Apress, 2023)
Overhaul your debugging techniques and master the theory and tools needed to debug and troubleshoot cloud applications in production environments. This book teaches debugging skills that universities often avoid, but that typically consume as much as 60% of our time as developers. The book covers the use of debugger features such as tracepoints, object marking, watch renderers, and more. Author Shai Almog presents a scientific approach to debugging that is grounded in theory while being practical enough to help you to chase stubborn bugs through the maze of a Kubernetes deployment. Practical Debugging at Scale assumes a polyglot environment as is common for most enterprises, but focuses on JVM environments. Most of the tooling and techniques described are applicable to Python, Node, and other platforms, as well as to Java and other JVM languages. The book specifically covers debugging in production, an often-neglected discipline but an all too painful reality. Youll learn modern techniques around observability, monitoring, logging, and full stack debugging that you can put to immediate use in troubleshooting common ailments in production environments. You Will Learn: The scientific method underlying the process of debugging Debugger capabilities such as tracepoints and marker objects The correct use of less understood features such as exception breakpoints Techniques for tracing issues in production Kubernetes environments Observability and monitoring to resolve production problems Industry best practices for common tooling such as logging Profiling to understand performance and memory problems .